Broken music a memoir - Sting Musiker 1951- (Dial Press, 2003)
Having been a songwriter most of my life, condensing my ideas and emotions into short rhming couplets and setting them to music, I had never really considered writing a book. But upon arriving at the reflective age of fifty, I found myself drawn, for the first time, to write long passages that were as stimulating and intriguing to me as any songwrting I had ever done. And so Broken Music began to take shape.
Keywords: Sting <(Musician)>; Sting -- Musiker -- 1951-; Musicians -- Biography; Rock musicians -- England -- Biography; Autobiografie